Microfluidic synthesis of high-valence programmable atom-like nanoparticles for reliable sensing. Issue 3 (20th December 2020) - Li, Jing; Shi, Huayi; Chen, Runzhi; Wu, Xiaofeng; Cheng, Jiayi; Dong, Fenglin; Wang, Houyu; He, Yao
Abstract : A novel synthetic strategy is presented for microfluidic preparation of programmable atom-like nanoparticles with high valences and high yields. Abstract : Synthesis of programmable atom-like nanoparticles (PANs) with high valences and high yields remains a grand challenge. Here, a novel synthetic strategy of microfluidic galvanic displacement (μ-GD) coupled with microfluidic DNA nanoassembly is advanced for synthesis of single-stranded DNA encoder (SSE)-encoded PANs for reliable surface-enhanced Raman scattering (SERS) sensing. Notably, PANs with high valences ( e.g., n -valence, n = 12) are synthesized with high yields ( e.g., >80%) owing to the effective control of interfacial reactions sequentially occurring in the microfluidic system. On the basis of this, we present the first demonstration of a PAN-based automatic analytical platform, in which sensor construction, sample loading and on-line monitoring are carried out in the microfluidic system, thus guaranteeing reliable quantitative measurement. In the proof-of-concept demonstration, accurate determination of tetracycline (TET) in serum and milk samples with a high recovery close to 100% and a low relative standard deviation (RSD) less than 5.0% is achieved by using this integrated analytical platform.